Foreign Direct Investment, Sovereign Debt and Growth: Evidence for the Euro Area - Tan, Ai-Lian; Ismail, Normaz Wana (American Journal of Trade and Policy, 2015)
In light of the global financial crisis, an extensive implementation of fiscal stimulus packages has triggered an enormous soared of public debt in Europe. While grappling with this albatross, the high debt level has aroused the paramount interest of this study casts doubt on the role of sovereign debt towards the linkage between FDI and economic growth. To this end, this study aims to assess the effects of debt on growth through the channel of FDI in European countries by applying Pooled Mean Group (PMG) estimation. The empirical findings, by and large, suggest that a lower growth performance is evident with the association of high government debt through foreign investment. In a nutshell, over borrowing of public finance would crowd out private investment and hence stifle economic growth. JEL Classifications Code: F21, F34, F43, G01